2007
DOI: 10.1177/070674370705201106
|View full text |Cite
|
Sign up to set email alerts
|

Combined Therapy of Major Depression with Concomitant Borderline Personality Disorder: Comparison of Interpersonal and Cognitive Psychotherapy

Abstract: Both combined therapies are efficacious in treating major depression in patients with BPD. Differences between CT and IPT concern specific features of subjective QOL and interpersonal problems. These findings lack reliable comparisons and need to be replicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 58 publications
2
42
0
Order By: Relevance
“…The findings in this area are also mixed, perhaps because they have focused on a range of pharmacological and psychotherapeutic treatments. Some work has suggested that individuals with comorbid personality pathology fare more poorly with IPT than with cognitive therapy (CBT; Beck, Rush, Shaw, & Emery, 1979; Carter et al, 2011; Joyce et al, 2007), and other work found that depressed individuals with comorbid borderline personality disorder fare equally well in treatment with IPT or CBT in addition to pharmacotherapy (Bellino, Zizza, Rinaldi, & Bogetto, 2007). In comparisons of psychotherapy and pharmacotherapy, both earlier (Tyrer, Seivewright, Ferguson, Murphy, & Johnson, 1993) and more recent work (Fournier et al, 2008; Maddux et al, 2009) suggest that individuals with comorbid Axis I psychopathology and personality disorders fare better with antidepressants, and those without a personality disorder fare better with psychotherapy.…”
mentioning
confidence: 99%
“…The findings in this area are also mixed, perhaps because they have focused on a range of pharmacological and psychotherapeutic treatments. Some work has suggested that individuals with comorbid personality pathology fare more poorly with IPT than with cognitive therapy (CBT; Beck, Rush, Shaw, & Emery, 1979; Carter et al, 2011; Joyce et al, 2007), and other work found that depressed individuals with comorbid borderline personality disorder fare equally well in treatment with IPT or CBT in addition to pharmacotherapy (Bellino, Zizza, Rinaldi, & Bogetto, 2007). In comparisons of psychotherapy and pharmacotherapy, both earlier (Tyrer, Seivewright, Ferguson, Murphy, & Johnson, 1993) and more recent work (Fournier et al, 2008; Maddux et al, 2009) suggest that individuals with comorbid Axis I psychopathology and personality disorders fare better with antidepressants, and those without a personality disorder fare better with psychotherapy.…”
mentioning
confidence: 99%
“…In previous studies performed by our group, 13,36 IPT has been efficaciously used to treat major depression in patients with concomitant BPD. However, data on treatment of core BPD symptoms with IPT are sparse.…”
mentioning
confidence: 99%
“…Klerman and colleagues explicitly argued in their 1984 manual that brief IPT was not intended to effect “personality change.” More recently, however, several investigative groups, including some of those originally trained by Klerman and Weissman, have attempted to adapt IPT for treatment of personality disorders (Markowitz, Bleiberg, Pessin, & Skodol, 2007; Bellino, Zizza, Rinaldi, & Bogetto, 2007). Despite disappointing results from an earlier trial (Angus & Gillies, 1994) that was largely focused on the depressive symptoms experienced by those with borderline personality disorder (BPD), Markowitz, Skodol, and Bleiberg (2006) adapted IPT for borderline personality disorder (BPD).…”
Section: Adaptations Of the Original Ipt Model For Specific Populationsmentioning
confidence: 99%
“…Markowitz, Skodol, and Bleiberg’s (2006, 2007) claim received some support from a subsequent study comparing IPT and CBT as treatments for individuals with depression and BPD, in which individuals (n=32) received either IPT plus pharmacotherapy or CT plus pharmacotherapy for 24 weeks (Bellino, Zizza, Rinaldi, & Bogetto, 2007). They found no difference between groups in proportions of participants who remitted from depression; however, IPT patients showed greater improvement in social functioning and in the domineering/controlling and intrusive/needy domains of the Inventory of Interpersonal Problems.…”
Section: Adaptations Of the Original Ipt Model For Specific Populationsmentioning
confidence: 99%